A thread of violence : a story of truth, invention, and murder - O'Connell, Mark, 1979- (Doubleday, 2023)
"From the award-winning author comes a gripping account of one of the most scandalous murder in modern Irish history, at once a propulsive work of true crime and an act of literary subversion. Malcolm MacArthur was a well-known Dublin socialite and heir. Suave and urbane, he passed his days mingling with artists and aristocrats, reading philosophy, living a life of the mind. But by 1982, his inheritance had dwindled to almost nothing, a desperate threat to his lifestyle. MacArthur hastily conceived a plan: He would commit bank robbery, of the kind that had become frightfully common in Dublin at the time. But his plan spun swiftly out of control, and he needlessly killed two innocent people. The ensuing manhunt, arrest, and conviction amounted to one of the most infamous political scandals in modern Irish history, contributing to the eventual collapse of a government. Wellcome and Rooney Prize-winning author Mark O'Connell spent countless hours in conversation with MacArthur--interviews that veered from confession to evasion. Through their tense exchanges and O'Connell's independent reporting, a pair of narratives unspools: a riveting account of MacArthur's crimes and a study of the hazy line between truth and invention. We come to see not only the enormity of the murders but the damage that's inflicted when a life is rendered into story. At once propulsive and searching, A Thread of Violence is a hard look at a brutal act, its subterranean origins, and the long shadow it casts. It offers a haunting and insightful examination of the lies we tell ourselves--and the lengths we'll go to preserve them"--